Genetic diversity in natural populations of the endangered Neotropical orchid Telipogon peruvianus. Issue 1 (9th September 2020) - Martel, Carlos; Scopece, Giovanni; Cozzolino, Salvatore; Ayasse, Manfred; Pinheiro, Fabio; Cafasso, Donata
Abstract: Telipogon peruvianus is a highly restricted, sexually deceptive, Neotropical orchid species, endemic to the southern Peruvian Andes. It is only known from two localities, which are affected by anthropogenic disturbance. Here, we investigated whether the restricted distribution of T. peruvianus has led to low genetic diversity and inbreeding, thus threatening its survival. We isolated 10 novel microsatellite loci specific for T. peruvianus (and that also cross‐amplified in related species) from two adjacent populations. We found that genetic diversity within populations was only moderately reduced, along with some evidence of inbreeding. We found low levels of genetic differentiation, suggesting connectivity by pollen/seed flow between the two populations. Effective population size was comparable to the real number of flowering individuals in the populations and we did not detect the signature of recent bottlenecks. Taken together, these results show that, despite increasing anthropogenic pressure, the two investigated populations of T. peruvianus still host valuable genetic diversity that should be preserved through appropriate conservation strategies. Abstract : Here, we investigated whether the restricted distribution of the highly restricted, sexually deceptive, Neotropical orchid species Telipogon peruvianus has led to low genetic diversity and inbreeding, thus threatening its survival. Our results show that, despite increasing anthropogenic pressure, the investigated populations of T. peruvianus still host valuable genetic diversity that should be preserved through appropriate conservation strategies.